ANALISIS PENDAPATAN DAN NILAI TAMBAH AGROINDUSTRI KERIPIK PISANG DI DESA SUNGAI LANGKA KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Shofia Salsabilla; Dwi Haryono; Yuniar Aviati Syarief (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
The purpose of this research is to study the income and added value of banana chips agroindustry.  The research location was chosen purposively at Sungai Langka village Pesawaran District by consideration that Banana Chips Agroindustry at Sungai Langka village was active routinely produce and also has a potential to be developed. Respondents were  the owners of banana chips agroindustries. The data were collected in Desember 2017 and analyzed by a quantitative descriptive analysis. The result of the research showed that the income based on total cost per month of banana chips agroindustry was Rp1,366,46.,67.  Banana Chips Agroindustry was viable because it has positive added value amounted Rp3,758.26/kg raw material and favorable for its R/C  value of more than one which are 1.37 at cash cost and 1.35 at total cost.Key words: added value, agroindustry, banana chips, income